“Checking a Box Isn’t Exactly Helpful”: Interpretations of the Voluntary Self-Identification of Disability Form During the Job Application Process - Duncan, Kaylin; Sias, Patricia M. (Disability Studies Quarterly, 2023)
The United States Department of Labor created the Voluntary Self-Identification of Disability (VSD) form in 2014 to improve the employment rate for people with disabilities. As part of this initiative, federal contractors with 50 or more employees are expected to have at least 7% of their workforce identify as having a disability. Unfortunately, only 13% of organizations met this goal in 2015. By conducting a survey of 472 individuals, the present study examined how people with and without disabilities interpret the Voluntary Self-Identification of Disability (VSD) form during the job application process. Specifically, respondents inferred positive (e.g., accommodations), negative (e.g., discrimination), neutral (e.g., person-job fit), and conflicting interpretations (e.g., a mix of positive and negative interpretations) of the VSD form. Further, nearly 60 percent of applicants perceived the VSD form as a strategy to decrease the number of people with disabilities rather than increase. With insight on organizational signals, employers and policymakers can better design and develop recruitment materials to improve the application process for people with disabilities.